2015
DOI: 10.1016/j.scr.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Cell aggregation optimizes the differentiation of human ESCs and iPSCs into pancreatic bud-like progenitor cells

Abstract: Embryonic pancreatic bud cells, the earliest pancreas-committed cells, generated from human embryonic stem cells (hESCs) and induced pluripotent stem cells (hiPSCs) have been shown to differentiate into mature pancreatic β-cells in vivo, indicating the feasibility of hESC/iPSC-based cell therapy for diabetes. However, the key factors required for the differentiation of these cells into pancreatic bud cells are incompletely understood. The purpose of this study was to establish culture conditions that efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 48 publications
5
88
0
1
Order By: Relevance
“…This suggests that formation of tight cell‐cell contacts from pre‐aggregation prior to encapsulation may be promoting differentiation. This is supported by the report by Toyoda et al showing that aggregation of human embryonic stem cells strongly enhances pancreatic bud differentiation …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This suggests that formation of tight cell‐cell contacts from pre‐aggregation prior to encapsulation may be promoting differentiation. This is supported by the report by Toyoda et al showing that aggregation of human embryonic stem cells strongly enhances pancreatic bud differentiation …”
Section: Discussionsupporting
confidence: 74%
“…Lee et al showed controlling hPSC colony size could control specification to mesoderm (1200 µm in diameter) or endoderm in the presence of soluble differentiation factors, linking cellular organization to hPSC differentiation . More specific to pancreatic differentiation, Toyoda et al demonstrated enhancement of pancreatic induction of hPSCs with increasing cell density in adherent (2D) cultures, which was further improved in aggregate culture . Thus clinical translation of encapsulated hPSCs will require a thorough evaluation of optimum parameters supporting hPSC growth and differentiation …”
Section: Introductionmentioning
confidence: 99%
“…Scale bars, 100 μm. Adapted from Toyoda et al . with permission (licensed under Creative Commons Attribution).…”
Section: Directed Differentiation Into Pancreatic β‐Cellsmentioning
confidence: 99%
“…By providing appropriate growth factors and substrates that closely mimic the relevant environment during embryonic development, IPS cells have been successfully coaxed to differentiate into numerous cell types, including those constituting glandular organs such as the liver and pancreas (Pagliuca et al, 2014; Ishikawa et al, 2015; Pellegrini et al, 2015; Toyoda et al, 2015). A similar strategy to that used for human embryonic stem cells (hESCs) (Lee et al, 2007; Dincer et al, 2013; Leung et al, 2013) can be applied to IPS cells to derive lacrimal gland tissues.…”
Section: The Molecular Mechanism Of Lacrimal Gland Developmentmentioning
confidence: 99%